2015
DOI: 10.12659/pjr.892105
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Imaging in a Patient with Cystic Thymoma: CT, MR and PET/CT Comparison

Abstract: SummaryBackgroundCystic thymoma is a rare variant of thymic neoplasm characterized by almost complete cystic degeneration with mixed internal structure. We describe a case of a 60 year-old woman with a cystic thymoma studied with advanced tomographic imaging stydies.CT, MRI and PET/CT with 18F-FDG were performed; volumetric CT and MRI images provided better anatomic evaluation for pre-operative assessment, while PET/CT was helpful for lesion characterization based on 18F-FDG uptake. Although imaging studies ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…The infiltration of surrounding fat, pleural nodules, elevated hemidiaphragm, and pulmonary nodules were identified as independent risk factors for patients with myasthenia gravis. These results were similar to those of previous studies (7, 21, 4548). Klimiec et al (16) suggested that routine CT imaging can effectively identify thymomas; however, radiologists should be cautious in interpreting these images when differentiating between thymic hyperplasia and a normal thymus in patients with myasthenia gravis, as they are not reliable.…”
Section: Discussionsupporting
confidence: 93%
“…The infiltration of surrounding fat, pleural nodules, elevated hemidiaphragm, and pulmonary nodules were identified as independent risk factors for patients with myasthenia gravis. These results were similar to those of previous studies (7, 21, 4548). Klimiec et al (16) suggested that routine CT imaging can effectively identify thymomas; however, radiologists should be cautious in interpreting these images when differentiating between thymic hyperplasia and a normal thymus in patients with myasthenia gravis, as they are not reliable.…”
Section: Discussionsupporting
confidence: 93%
“…Complete surgical removal of the thymic tumors with the involved adjacent structures is hence the popular treatment modality ( 11 ). A special subgroup of thymic tumors is the cystic thymus tumor that is characterized by multiple cysts ( 12 ). The 18 F-FDG PET/CT imaging may demonstrate an increased uptake in the cystic thymomas related to the septum or margins of the tumor ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…A special subgroup of thymic tumors is the cystic thymus tumor that is characterized by multiple cysts ( 12 ). The 18 F-FDG PET/CT imaging may demonstrate an increased uptake in the cystic thymomas related to the septum or margins of the tumor ( 12 ). The SUV max cut-off level for malignant and benign thymomas have not been determined, although the previous reports accepted the 4.5-6.3 levels ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…One aspect worth mentioning is that thymoma may undergo cystic degeneration and show a predominantly cystic appearance (22). There was no cystic thymoma in our population, and our criteria may not work in cystic thymomas.…”
Section: Discussionmentioning
confidence: 99%